Transmembrane activator and calcium-modulating cyclophilin ligand interactor mutations in common variable immunodeficiency: Clinical and immunologic outcomes in heterozygotes - Zhang, Li (2007)
BACKGROUND: Mutations in the gene coding for transmembrane activator and calcium-modulating cyclophilin ligand interactor (TACI) have been identified in common variable immunodeficiency (CVID). Mutations coincided with immunodeficiency in families, suggesting dominant inheritance. OBJECTIVE: Because most subjects with CVID have no immunodeficient family members and heterozygous mutations predominate, the role of TACI mutations in sporadic CVID is unclear. METHODS: TACI was sequenced from the genomic DNA of 176 subjects with CVID and family members. B cells of subjects with or without mutations were examined for binding to the ligand, a proliferation inducing ligand (APRIL), and for proliferation and immunoglobulin production after ligand RESULTS: Heterozygous TACI mutations were found in 13 subjects (7.3%). Six with mutations (46%) had episodes of autoimmune thrombocytopenia, in contrast with 12% of 163 subjects without mutations; splenomegaly and splenectomy were significantly increased (P = .012; P = .001.) B cells of some had impaired binding of APRIL and on culture with this ligand were defective in proliferation and immunoglobulin production; however, this was not different from B cells of subjects without mutations. Eight first-degree relatives from 5 families had the same mutations but were not immune-deficient, and their B cells produced normal amounts of IgG and IgA after APRIL stimulation. CONCLUSION: Mutations in TACI significantly predispose to autoimmunity and lymphoid hyperplasia in CVID, but additional genetic or environmental factors are required to induce immune deficiency. CLINICAL IMPLICATIONS: Additional causes of this common immune deficiency syndrome remain to be determined.